Cytokine Storm Syndrome in SARS-CoV-2 Infections: A Functional Role of Mast Cells - Bahareh Hafezi; Lily Chan; Jason P. Knapp; Negar Karimi; Kimia Alizadeh; Yeganeh Mehrani; Byram W. Bridle; Khalil Karimi (Cells, 2021)
Cytokine storm syndrome is a cascade of escalated immune responses disposing the immune system to exhaustion, which might ultimately result in organ failure and fatal respiratory distress. Infection with severe acute respiratory syndrome-coronavirus-2 can result in uncontrolled production of cytokines and eventually the development of cytokine storm syndrome. Mast cells may react to viruses in collaboration with other cells and lung autopsy findings from patients that died from the coronavirus disease that emerged in 2019 (COVID-19) showed accumulation of mast cells in the lungs that was thought to be the cause of pulmonary edema, inflammation, and thrombosis. In this review, we present evidence that a cytokine response by mast cells may initiate inappropriate antiviral immune responses and cause the development of cytokine storm syndrome. We also explore the potential of mast cell activators as adjuvants for COVID-19 vaccines and discuss the medications that target the functions of mast cells and could be of value in the treatment of COVID-19. Recognition of the cytokine storm is crucial for proper treatment of patients and preventing the release of mast cell mediators, as impeding the impacts imposed by these mediators could reduce the severity of COVID-19.